De la oscuridad a la nueva luz: entre tradición y leyenda. «Calle sin nombre» de Claudio Rodríguez - Mistrorigo, Alessandro (Dicenda. Estudios de lengua y literatura españolas, 2003)
The character of frontier and limit between previous tradition and the latest poetic expression of Claudio Rodríguez which is represented by the poem Calle sin nombre— allows us to read his poetry from a new point of view. Darkness as a basic symbol of the poetry of revelation. A privileged symbolic place for contemplation and revelation in which the origin of the poetic process itself spreads. Darkness as a «seed» of poetry, spreading cause of the latest poetry of Rodríguez: the light of revelation shows itself from the symbolic ambivalence of this obscure setting.